2017
DOI: 10.1007/s10897-017-0173-9
|View full text |Cite
|
Sign up to set email alerts
|

Challenges, Dilemmas and Factors Involved in PGD Decision‐Making: Providers’ and Patients’ Views, Experiences and Decisions

Abstract: Providers and patients are considering and pursuing PGD for ever-more conditions, but questions arise concerning how they make, view and experience these decisions, and what challenges they may face. Thirty-seven in-depth semi-structured interviews were conducted (with 27 IVF providers and 10 patients). Patients and providers struggled with challenges and dilemmas about whether to pursue PGD in specific cases, and how to decide. Respondents varied in how they viewed, experienced and made these choices, and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…With the results of this study, bearing in mind that this is a study regarding the hypothetical use of future technologies, we attempted to gain more insight into the future dynamics of the reproductive decision-making process of high-risk couples counselled for PND and/or PGT who want to avoid the birth of an affected child. Understanding these couples’ perspectives can assist in navigating reproductive decision-making [ 7 ]. Genetic counsellors could bear in mind the concepts underlying decision-making identified in this study, and explore together with couples how they feel about the different options and support them in their decision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the results of this study, bearing in mind that this is a study regarding the hypothetical use of future technologies, we attempted to gain more insight into the future dynamics of the reproductive decision-making process of high-risk couples counselled for PND and/or PGT who want to avoid the birth of an affected child. Understanding these couples’ perspectives can assist in navigating reproductive decision-making [ 7 ]. Genetic counsellors could bear in mind the concepts underlying decision-making identified in this study, and explore together with couples how they feel about the different options and support them in their decision.…”
Section: Discussionmentioning
confidence: 99%
“…Other reproductive options are: refraining from having (more) children, using donor sperm or donor oocytes, considering adoption, or accepting the risk. Reproductive decision-making for high-risk couples is complex and known to be influenced by several factors, including the severity of the condition [ 2 6 ] , experiences with the condition [ 1 4 , 6 , 7 ], having an affected child [ 3 , 5 , 8 ], attitudes towards pregnancy termination [ 1 , 6 8 ], the desire to have genetically related children [ 1 , 8 ] , and perceptions on new technologies and their characteristics (e.g. safety) [ 1 , 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This has been reported in six studies and is illustrated in Figure 2. In particular, one study reported that patients did not understand what PGT was, even though they were in favour of the idea of PGT (Klitzman, 2018). Therefore, they preferred to have more education about this technique, especially education on what conditions were suitable for performing PGT (Klitzman, 2018).…”
Section: Enablers Of Decision-making: Pgt-m and Pgt-sr Setting (A) Information Directly Relevant To Pgt Treatmentmentioning
confidence: 99%
“…With wide application of PGT, there is an increasing research interest in improving patient care for those using PGT, including patients" decisionmaking. However, making a decision regarding whether or not to undergo PGT is complex, since it involves various factors such as success rates, procedural safety, financial costs, burden of disease, past obstetric history, religious beliefs and ethical values (Gebhart et al, 2016;Hershberger and Pierce, 2010;Klitzman, 2018;van Rij et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the ability that patients have to process their health information and their reactions to it are affected by provider education and recommendations. Using a sample of 27 infertility providers (4 of whom were also patients) and 10 patients, Klitzman (2018) described how the providers’ experience and knowledge of PGT and genetics influence their referral/recommendations about PGT to patients. Therefore, in addition to the patient’s own attitude and knowledge about PGT, providers’ attitudes and knowledge also have an impact on patients, in terms of whether they are referred for PGT counseling or if testing is recommended.…”
Section: Introductionmentioning
confidence: 99%